Preconceito Linguístico: entre o desconhecimento e o negacionismo. Uma análise de comentários em redes sociais - Luchessi, Emerson Matheus (Universidade Federal de São Carlos, 2022)
The present work intended to identify and present the manifestations and possible regularities of linguistic prejudice in social network comments on two videos dealing with the popular language spoken in Brazilian Portuguese, through approaches of the scientific knowledge of language. The analyzed comments were submitted to a descriptive research of qualitative approach, with the intention of identifying their regularities. It was thus revealed that linguistic prejudice is connected to a large extent to the ignorance of linguistic science, but manifestations aligned with the negation of this science stand out in the research. This work is based on the studies by Bagno (2015) and Scherre (2005) on linguistic prejudice, and on approaches with emphasis on sociolinguistics through the work of Alckmin (2012), Coelho et. al (2015), Mollica and Braga (2013), among others.
Linguistic prejudice:between unknowledge and negationism. An analysis of comments on social networks
Keywords: Preconceito linguístico; Ciência linguística; Negacionismo; Redes sociais; Linguistic prejudice; Linguist Sciense; Negationism; Social media; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::FISIOLOGIA DA LINGUAGEM; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA